Numerical and Physical Model Analysis Comparison for Velocity of Water at Spillway - Zaki S.A.A.; Hassan N.H.; Zawawi M.H.; Abas M.A.; Mazlan A.Z.A.; Zainol M.R.R.M.A.; Radzi M.R.M. (Springer, 2023)
High velocity may affect the structure integrity due to long exposure. Thus, this study was done to assess velocity specifically at energy dissipater and stilling basin of Chenderoh Dam spillway by numerical and physical model analysis. A 3D model drawing of 1:20 scaled had be drawn to be analysed and as a reference for physical model development. Numerical model had been analysed based on the fundamental of computational fluid dynamic (CFD). Physical model of the spillway has been developed to verify the accuracy of numerical model analysis. The result shows that both of the difference percentage at energy dissipater and stilling basin for velocity are less than 10% which are 4.3135% and 4.1879% respectively. Therefore, the numerical and physical model result for 1:20 scale model can be used to validate this dam numerical simulation result up to 95% precision. 2020, Springer Nature Singapore Pte Ltd.